Hubungan Antara Kontrol Diri dan Motivasi Belajar dengan Kedisiplinan Siswa SMA As-syafi’iyah Medan - Saparudin Sari; Abdul Murad; Azhar Aziz (Universitas Medan Area, 2020)
This research aimed, to know the relationship between self-control to students’ discipline students. to know the relationship between motivation of study to student’s discipline students, to know the relationship between self-control and motivation of study to student’s discipline students. The populations of the study are total students of class X and XI SMA AS-SYAFI’IYAH MEDAN consisted of 135 students. so sample set to the Purpossive Samplingtechnique consisted 80 students. The research data were gathered based on scale sefl-controlandstudy motivation. The shape of scale used likert scale, consisted of 30 shapes self-control variables of (XI) either 30 variables of (X2). The data analysis used of RegresiBerganda, and the result of the research indicated there was significant relationship between self-control and students’ discipline about R=0,547 and p=0,000. Significant relationship between motivation of study and discipline of study about R= 0,299and p=0,001. Significant relationship between self-control and study motivation to the students’ discipline about F=33,269 and p=0,000.